Association of dietary intake and dietary habits with risk of cardiovascular disease among immigrant Pakistanis living in the Netherlands - Qaisar Raza; Mary Nicolaou; Funda Cay; Jaap Seidell (Journal of the Pakistan Medical Association, 2020)
Objective: To explore the current intake/changed dietary habits being associated with risk of cardiovascular disease after migration from Pakistan to the Netherlands. Methods: Data collection started in March 2012 and ended in July 2013. Self-administered survey with respect to cardiovascular disease and dietary intake was filled by 154 adult Pakistanis. Participants were approached through festivals and community centres. Descriptive statistics was used to analyse the data. Results: There were 41 (61%) participants who reported drinking fruit juice every day, while 13 (18.6%) participants reported drinking soft drinks 5-7 days a week. In addition, 20 (30%) participants reported decreased intake of high fat/fried foods, deserts/candy/sweets and red meat, while 23 (35%) reported an increased intake of soft drinks and convenience foods, as far as high calorie and refined food items were considered, after migration. Conclusion The study showed significant changes in dietary habits, both favourable and unfavourable, being associated with risk of cardiovascular diseases among immigrant Pakistanis living in The Netherlands. Key Words/MeSh Words: Pakistani; CVD; Migration; Diet; Dietary acculturation